Cover Image. (14th August 2019) - Liu, Juan; Wang, Yixiang; Meng, Huanxin; Yu, Jingting; Lu, Hongye; Li, Wenjing; Lu, Ruifang; Zhao, Yibing; Li, Qiqiang; Su, Li
Abstract : The cover image is based on the Original Article Butyrate Rather than LPS Subverts Gingival Epithelial Homeostasis by Downregulation of Intercellular Junctions and Triggering Pyroptosis by Juan Liu et al., DOI: 10.1111/jcpe.13162 .